Isozyme analysis and its application in plant breeding - Asiedu, Robert (1992)
Plant breeders face the difficult task of having to select for traits that are often under complex genetic control and subject to edapho-climatic influences. Electrophoresis of protein extracts from plant tissue, using different kinds ofsupport media and buffer systems, allows separation of the multiple forms ofenzymes (isozymes) on the basis of charge and/or molecular size. The resulting polymorphisms are useful as genetic markers. Isozyme analysis is a powerful technique for estimating genetic variability, identifying cultivars and germplasm accessions, confirming hybrids, tracking alien chromosome segments, tagging genes, and screening backcross populations more efficiently.